2019
DOI: 10.1029/2019gc008720
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Inflation During a Noneruptive Episode of Seismic Unrest at Semisopochnoi Volcano, Alaska in 2014–2015

Abstract: Magma intrusion rate is a key parameter in eruption triggering but is poorly quantified in existing geodetic studies. Here we examine two episodes of rapid inflation in this context. Two noneruptive microseismic swarms were recorded at Semisopochnoi Volcano, Alaska in 2014-2015. We use differential SAR techniques and TerraSAR-X images to document surface deformation from 2011 to 2015, which comprises island-wide radial inflation totaling~25 cm (+/−1 cm) line of sight displacement in 2014-2015. Multiple source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 88 publications
2
7
0
Order By: Relevance
“…The largest earthquake (M2.7) did not occur until November 15 and there were 22 earthquakes with magnitude greater than two; however, none of those happened on the first two days of the swarm, when the rate was highest. The rates, magnitudes, and durations of the swarm at Little Sitkin are similar to other recent non-eruptive swarms at nearby Semisopochnoi volcano (DeGrandpre et al, 2019).…”
Section: Observationssupporting
confidence: 74%
“…The largest earthquake (M2.7) did not occur until November 15 and there were 22 earthquakes with magnitude greater than two; however, none of those happened on the first two days of the swarm, when the rate was highest. The rates, magnitudes, and durations of the swarm at Little Sitkin are similar to other recent non-eruptive swarms at nearby Semisopochnoi volcano (DeGrandpre et al, 2019).…”
Section: Observationssupporting
confidence: 74%
“…Several thousand recorded volcano-tectonic events may have marked magmatic intrusion; however, none resulted in a magmatic eruption. Interferometric synthetic aperture radar (InSAR) observations were used to evaluate ground deformations during this unrest, and DeGrandpre et al 24 reported more than 25 cm of total inflation during 2003 and up to June 26, 2014, of which more than half occurred in the ten days between June 15 and 26, 2014. In June, the inflation rate reached 6 mm per day 24 , with inflation occurring as a simple radial pattern centered inside the caldera with a slight northeast–southwest oblique skew.…”
Section: Introductionmentioning
confidence: 99%
“…Interferometric synthetic aperture radar (InSAR) observations were used to evaluate ground deformations during this unrest, and DeGrandpre et al 24 reported more than 25 cm of total inflation during 2003 and up to June 26, 2014, of which more than half occurred in the ten days between June 15 and 26, 2014. In June, the inflation rate reached 6 mm per day 24 , with inflation occurring as a simple radial pattern centered inside the caldera with a slight northeast–southwest oblique skew. After June 26, 2014, the ground deformation almost ceased until resuming during another episode of seismic activity from January to May 2015 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations